2012
DOI: 10.1007/s12325-012-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Safety of the Intradermal Influenza Vaccine Among the Elderly in Italy: an On-Field National Study

Abstract: The novel ID influenza vaccine can be widely recommended in clinical practice, representing a useful tool to improve immunization coverage rates, and thus the control of influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…[16][17][18] In particular, the rates of solicited reactions up to 14 days following immunization resulted lower than those reported in other similar clinical trials performed in the elderly, both previously immunized with PPV23 and pneumococcal vaccine-naive: this could also be related to the study design and to the method used for data collection (self-administered clinical diary for data collection in the first week following immunization and phone call by health-care professionals at day 21 for data collection in the second week after vaccination). Fever rates, commonly recorded in children after vaccination with PCV13, 26 were low (2.2%) among the elderly in our study, and no sudden reaction following immunization, nor deaths occurred during the follow up.…”
Section: Discussioncontrasting
confidence: 46%
“…[16][17][18] In particular, the rates of solicited reactions up to 14 days following immunization resulted lower than those reported in other similar clinical trials performed in the elderly, both previously immunized with PPV23 and pneumococcal vaccine-naive: this could also be related to the study design and to the method used for data collection (self-administered clinical diary for data collection in the first week following immunization and phone call by health-care professionals at day 21 for data collection in the second week after vaccination). Fever rates, commonly recorded in children after vaccination with PCV13, 26 were low (2.2%) among the elderly in our study, and no sudden reaction following immunization, nor deaths occurred during the follow up.…”
Section: Discussioncontrasting
confidence: 46%
“…84,85 In routine clinical practice the ID influenza vaccine showed a good safety and acceptance profile and an optimal compliance to its use was registered among vaccine prescribers. 86 During the last years the ID route of administration has been extensively studied in order to assess immunogenicity of different influenza vaccine formulations and in different population targets.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established barrier to influenza immunization is a general lack of patient acceptance of traditional intramuscular vaccination: recent studies have demonstrated that the most common reasons for missing previous vaccinations are fear of adverse events, bothered by pain during injection and dislike for injections or needles, and that other ways of vaccine administration were considered to be an encouraging alternative to implement vaccination against influenza. [12][13][14][15][16][17][18][19] For all these reasons, new vaccines providing (1) a robust, effective and protective antibody response in patients with impaired innate and adaptive immunity, such as older people or patients with chronic diseases, (2) a broader and cross-reactive immune response against drifted influenza variants and (3) an excellent safety, tolerability and acceptability profile are urgently needed. Among several strategies explored to enhance immunogenicity of plain -subunit and split -vaccines, the use of adjuvants (i.e., MF59 ® ), or carriers, (i.e., virosome), have led to licensed vaccines in Europe, while intradermal administration of influenza vaccine has emerged as a promising option, thanks to the recent availability of a new delivery device.…”
Section: Head-to-head Comparison Of An Intradermal and A Virosome Infmentioning
confidence: 99%